The Site Of Rebah City, Abandoned Historical Witness - Kamaruzaman M.M.; Romi Aqmal; Ainul Mutaqhoro; Dicky Yuspriandi (Advances in Humanities and Contemporary Studies, 2021)
The site of Rebah City or Kota Lama is a historical relic was a legacy of the Johor Sultanate which was previously used as the center of government, but now it has abandoned and no longer maintained. This place is getting quietly. The number of visitors who come to this place are also getting smaller. Objective if the study is to produce studies that can be input for the improvement of this historical heritage site. Research found that there are some of the historical relic that still available in there such as tombs, ruins of building and old houses. Besides, there are some of the public facilities have built by the government such as gazebo, port, rest area, praying room and etc. From this, we can realize that the government and society are less capable of preserving the existing historical heritage. This is proven by the poor maintenance of the Istana Kota Lama which was once the seat of the Johor Kingdom government. In this visit, the writer hopes for the preservation of this historic site, where this place is a historical witness and becomes evidence of past civilizations.